Structural response of the U-type corrugated core sandwich panel used in ship structures under the lateral quasi-static compression load. (July 2022) - Liu, Kun; Zong, Shuai; Li, Yao; Wang, Zeping; Hu, Zhiqiang; Wang, Zili
Abstract: This paper addresses a study on the structural deformation mechanism of the U-type corrugated core sandwich panel used in ship structures under the lateral quasi-static compression load through the experimental, numerical and analytical methods. Based on the results from quasi-static experiment and the finite element simulation, the deformation characteristics of the U-type corrugated core sandwich panel under the lateral quasi-static compression load are analyzed. The results show that the deformation of the U-type corrugated core sandwich panel can be divided into two processes according to whether the core is in contact during the compression process. And the deformation process has little influence on the variation trend of the structural resistance curve. Based on this, the deformation mode of the U-type corrugated sandwich panel is summarized, and the analytical formula of the deformation resistance of the U-type corrugated core sandwich panel is developed. It is shown that the proposed theoretical deformation model can reflect the main deformation process, and the analytical results match well with the experimental and numerical results. Highlights: The structural deformation mechanism of the U-type corrugated core sandwich panel under the lateral quasi-static compression load is researched through the experimental, numerical simulation and analytical methods. Based on the results from quasi-static experiment and the numerical simulation, the deformation characteristics of the U-type corrugated core sandwich panel are analyzed. The deformation mode of the U-type corrugated sandwich panel is proposed, and the analytical calculation formula of the deformation resistance is deduced. The proposed theoretical deformation model can reflect the main deformation process, and the analytical results match well with the experimental and numerical results. The analytical model proposed is of important engineering application value for the ship structural design and anti-impact performance evaluation of the corrugated core sandwich panel.